La Química de Superficies y su Relación con la Microelectrónica - Rodríguez-Reyes, Juan Carlos F. (2007)
Surface Chemistry and its Relation to MicroelectronicsCircuits forming part of any electronic device are more efficient, but at the same time the dimension s of theircomponents are reduced constantly and they will soon reach the atomic scale. Each component has to be carefully deposited as a thin film on a surface which, on the atomic scale, is only possible if the chemical reactions involved in the process areunderstood and controlled. This article describes initially the techniques for thin film formation on substrates, emphasizingthe current importance of organometallic compounds during this process. For example, one of these compounds, tetrakis-(dimethylamido)-titanium(IV), Ti[N(CH ) ] , is used, together with ammonia (NH3), for the formation of titanium nitride films. The reaction of both compounds with a silicon surface is investigated, and it is found that in both cases the reaction starts through the interaction of a N lone pair with the surface, followed by dissociation of molecules. The elucidation of these mechanisms are important not only for controlling the thin film deposition processes, but also for the growing field of molecular electronics, where the formation of molecular architectures of the surface is a requisite. This article also includes a brief review of selected topics related to surface chemistry that are relevant for the present investigation, such as the types of surface reactions, properties of the silicon surface and the use of spectroscopic and computational techniques in this field.